The expectant father : the ultimate guide for dads-to-be - Brott, Armin A.; Ash, Jennifer (New York : Abbeville Press, 2015)
"The fourth edition of this best-selling, ground-breaking, information-packed guide for dads-to-be is now significantly, updated, revised, and expanded. We are expecting! The twentieth-anniversary edition of this thoroughly updated and revised parenting classic remains the most informative and reassuring book for expectant fathers everywhere. In addition to sharing the wisdom of the ages, Armin A. Brott, Mr. Dad, presents new insight into the emotional, financial, and physical-yes, physical-effects of impending parenthood on men. Thanks to this handy reference moms-to-be will know their partner understands and supports them during this anxious and exciting time, and that he has all the tools he needs to be a fantastic, hands-on dad. This information-packed, month-by-month guide incorporates the expertise of top practitioners in their fields, from obstetricians and birth-class instructors to psychologists and sociologists. It also draws from Brott's own experience as a father of three and from the real-world experiences of the thousands of dads he's interviewed. With the humor of New Yorker cartoons and Brott's gentle approach, The Expectant Father serves as a friendly and readable companion for dads-to-be seeking confidence, guidance, and joy! What's new in this edition of The Expectant Father? - The latest health and safety info - How technology is changing fatherhood - How men's brains change by being involved during pregnancy - Society's shifting expectations for dads - The amazing effects on children when fathers are active partners before birth - How pre-birth participation makes dads more likely to be active parents post-birth - Updated resources. and new research on the big questions that haven't changed much over the years - Am I really ready to be a dad? - How are we going to afford this? - How do I balance work and family? - Will I be able to handle labor and delivery while being there for my partner? - What if something goes wrong? - How
"An expanded and updated month-to-month guide to the emotional, financial, and physical changes the father-to-be may experience during his partner's pregnancy"--
will this affect my relationship with my partner? - Will we ever have sex again? - What am I supposed to do with a new baby? - How can I be a good dad? - Will I ever see my friends again or have any time to myself?"--
Revised edition of the authors' The expectant father, 2010.
Includes bibliographical references (pages 310-320) and index.
Includes bibliographical references and index.
Keywords: Fathers; Pregnancy -- Popular works; FAMILY & RELATIONSHIPS / Parenting / Fatherhood